Effect of Air Quality on the Mucosal Immune Molecules in Outdoor Male Athletes - Ming-Ru Chiang; Tung-Lin Lu; Chi-Cheng Lu; Yi-Ying Chen; Shih-Hua Fang (Journal of Physiological Investigation)
Elevated concentrations of particulate matter 2.5 (PM2.5) can harm the human respiratory system. Athletes training outdoors in polluted environments may face an increased risk of exposure. Few studies have reported on the effects of air quality on the mucosal immunity of athletes. In this study, we recruited 32 male athletes and employed a randomized crossover design. Each participant provided 2 ml of saliva sample before and after their regular 2-h exercise sessions on days with and without air pollution. The immune molecules in saliva, including immunoglobulin A, lysozyme, α-amylase, and nitric oxide (NO), were measured. The results indicated that exercise on PM2.5-polluted days resulted in significantly higher post-exercise salivary NO levels compared to those on nonpolluted days and led to an increase in α-amylase activity compared to the pre-exercise condition. For the 16 atopic participants, the post-exercise salivary NO levels on PM2.5-polluted days were significantly elevated than nonpolluted days. Although athletes without a history of allergic conditions exhibited similar changes, the magnitude of these responses was less pronounced. In conclusion, PM2.5 pollution induces physiological stress and inflammatory responses in athletes, particularly those with allergies. More research is needed to determine the chronic effects of air quality on the mucosal immunity of outdoor athletes.